Pueblerinos antioqueños en Medellín. La inmigración pueblo-ciudad a partir de un estudios de caso, 1940-1970 (2014)
ABSTRACT: During the twentieth century, Medellín, as other Colombian cities, experienced a remarkable population growth, which did not correspond with vegetative growth, but rather was the result of waves of immigrants arriving mainly from the villages of Antioquia. Newcomers saw an opportunity for personal progress, as the city was the economic, political, social and cultural epicenter of the region. The theory that violence and forced displacement was the main factor in the growth of Medellín is debated and contested in this article. The authors argue that the educational and employment opportunities offered by the city were much more meaningful to migrants. The research that supports this article used a case study to understand groups, institutions and individuals, establishing regularities and identifying peculiarities. The procedures used were data collection, data reduction, data analysis and the presentation of results, aimed at furthering understanding and answering research questions.